Prevalence of smoking and substance use in adolescents - Mete, Burak; Söyiler, Vedat; Pehlivan, Erkan (Journal of Dependence, 2020)
Objective: The aim of this study was to determine the prevalence of smoking and substance use among young people aged 14-18 years in Bingöl and to determine the relationship between smoking and substance use.Method: This is a cross-sectional study. It was built on 1235 students in 14 high schools in Bingöl city center. The stratified sampling method was used as the sampling method.Results: The prevalence of smoking among all students was 15.8%, the prevalence of using any addictive substance other than cigarette smoking was 5%. The prevalence of smoking was found to be 24.1% in male students, 7.7 in female students, the prevalence of any addictive substance use among male students was found to be 8.2% and 1.9% for female students. The risk of using any addictive substance other than smoking is 8 times higher in smokers and 2.5 times in men. At the age of 18, the risk of substance use other than smoking increases by 1.5 times. High school grade 2 is the critical period for starting smoking and substance use.Conclusion: Detrimental behaviors such as smoking and substance use are high in adolescents. Smoking also increases the risk of other addictive substances.
Keywords: Smoking; substance abuse; adolescent